Securing online evidence in civil cases: the legal perspectives - Mohamed, Duryana (2014)
Evidence is very important in establishing and proving any cases. Generally, only reliable and authentic evidence is admissible in the court of law. In civil cases such as online defamation and online breach of data or confidential information parties are required to establish their case on the balance of probabilities. This means, in order to succed in civil action against the defendant the plaintiff shall establish that there is a cause of action against the defendant. For instance, there is evidence that the defendant has uttered defamatory statement and the statement is published widely. In this situation, the plaintiff needs to produce good and reliable evidence either by oral submission or by written statement. However, before producing such evidence both parties need to know the appropriate methods of securing online evidence. If there is lack of care, the evidence may be lost, tampered or deleted during the process of securing such evidence. This paper will discuss on the methods of securing online evidence and their position under the Malaysian laws and procedures. (172 words)